2022
DOI: 10.1186/s12902-022-01222-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia screening based on survey data: an international instrument based on WHO STEPs dataset

Abstract: Background Hyperglycemia is rising globally and its associated complications impose heavy health and economic burden on the countries. Developing effective survey-based screening tools for hyperglycemia using reliable surveillance data, such as the WHO STEPs surveys, would be of great importance in early detection and/or prevention of hyperglycemia, especially in low or middle-income regions. Methods In this study, data from the nationwide 2016 STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Studies have developed predictive models (39,40) based on supervised ML (logistic regression, XG Boost, decision tree etc.) and some studies identi ed associated risk factors (41,42) using clustering algorithms (like principal component analysis), logistic regression classi er and other supervised ML algorithms. Predicative models for hypertension were developed by using population based datasets (43), with association of risk factors like high waist circumference (44), cognitive impairment (45) and sleep & pulmonary measures(46) were discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have developed predictive models (39,40) based on supervised ML (logistic regression, XG Boost, decision tree etc.) and some studies identi ed associated risk factors (41,42) using clustering algorithms (like principal component analysis), logistic regression classi er and other supervised ML algorithms. Predicative models for hypertension were developed by using population based datasets (43), with association of risk factors like high waist circumference (44), cognitive impairment (45) and sleep & pulmonary measures(46) were discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have developed predictive models [ 34 , 35 ] based on supervised ML (logistic regression, XG Boost, decision tree, etc.) and some studies identified associated risk factors [ 32 , 33 ] using clustering algorithms (like principal component analysis), logistic regression classifiers, and other supervised ML algorithms. Predicative models for hypertension were developed by using population-based datasets [ 39 ], with the association of risk factors like high waist circumference [ 38 ], cognitive impairment [ 37 ], and sleep & pulmonary measures [ 36 ] discussed.…”
Section: Resultsmentioning
confidence: 99%